2021
DOI: 10.3390/plants10081691
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Diversity and Antioxidant Capacity of the Service Tree (Sorbus domestica L.) Fruits from Two Eco-Geographical Regions

Abstract: Service tree, Sorbus domestica L., is a rare and neglected wild fruit tree species of southern and central Europe. Being distributed in different eco-geographical regions, with fragmented and low-density populations, S. domestica represents an interesting model case for investigating patterns of within- and between-population diversity at geographical and environmental scales. This study aimed to analyze the proximate composition, antioxidant activity, and morphometric fruit characteristics. We examined the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Focusing only in Sorbus fruits, there also are some researchers who reported some results comparing different maturity stages, 89 different parts of the fruit, 90 different genotypes, 67,71 different harvesting dates, 91 and different locations, 92,93 all reporting values of the same range of magnitude as the results reported here.…”
Section: Resultssupporting
confidence: 66%
“…Focusing only in Sorbus fruits, there also are some researchers who reported some results comparing different maturity stages, 89 different parts of the fruit, 90 different genotypes, 67,71 different harvesting dates, 91 and different locations, 92,93 all reporting values of the same range of magnitude as the results reported here.…”
Section: Resultssupporting
confidence: 66%
“…The lowest (0.71%) TA value was recorded in the 14MR02 genotype (Table ). In a study investigating TA values in service tree fruits, acidity values ranged from 0.64 to 0.74% . In a study conducted in service tree fruits, TA values were found between 5.9 and 12.2% .…”
Section: Resultsmentioning
confidence: 98%
“…In a study investigating TA values in service tree fruits, acidity values ranged from 0.64 to 0.74%. 39 In a study conducted in service tree fruits, TA values were found between 5.9 and 12.2%. 35 In a study conducted on service tree fruits in Kocaeli province, the highest TA value was found to be 0.42%.…”
Section: Resultsmentioning
confidence: 98%
“…Likewise, the locality is characterized by the lowest precipitation sums and the highest mean air temperatures during growing season. Therefore, higher content of antioxidants and secondary metabolites in the seedlings of populations Prnjavor probably represents the drought-tolerance mechanism aimed at neutralization of reactive oxygen species, and, consequently, avoidance of the oxidative damages caused by water stress (Mechri et al, 2020;Poljak et al, 2021). For example, Visi-Rajczi et al (2021) reported that European beech provenances originating from warmer climate were characterized by higher enzyme activity.…”
Section: Multivariate Patterns Support the Genetic Variability Of Wil...mentioning
confidence: 99%
“…Recent studies showed that multivariate statistical analyses can be efficiently used for evaluation of the phenotypic diversity, providing a valuable information on the species variability patterns and multi-traits relationships (Ganopoulos et al, 2015). In addition, these analyses proved particularly useful for characterization of extensive data sets consisting of large number of parameters (see Petruccelli et al, 2013;Moradi et al, 2020;Poljak et al, 2021). Hence, our research assessed the variability of populations and half-sib lines of wild cherry, originating from natural populations in Bosnia and Herzegovina, using a set of morphological, anatomical, physiological and biochemical traits.…”
Section: Introductionmentioning
confidence: 99%